Gambaran Capaian Standar Pelayanan Minimal (SPM) Kesehatan dengan Kasus Hipertensi dan Diabetes Melitus di Jawa Timur Tahun 2022 - Rindy Asti Pratami; Maki Zamzam; Faridha Cahyani (Yayasan Literasi Sains Indonesia, 2023)
Quality Service Standards or SPM are regulations regarding the type and quality of basic services that must be owned by the state, which at least are obtained by every citizen without exception. The prevalence of hypertension in East Java Province is 36.32%, while the prevalence of Diabetes Mellitus (DM) is 2.6%. This value is estimated by the large population in East Java who suffer from hypertension and DM. The purpose of this study was to describe the description of the achievement of Minimum Service Standards (MSS) indicators in the health sector in cases of hypertension and diabetes mellitus in East Java Province in 2022. The research method was a descriptive study with a retrospective design using secondary data screening on the achievement of MSS service targets in the health sector in cases of hypertension and diabetes mellitus in East Java Province. The research results obtained were that the percentage of achievement of MSS in the health sector in cases of hypertension and DM had increased from 2020 to 2022. As many as 38 regencies/cities in East Java Province had total achievement of MSS for hypertension and DM services in East Java Province at number 58% and 96%. As many as 17 out of 38 districts/cities in East Java Province whose percentage score for achievement of MSS is below the total percentage for achievement of hypertension MSS in East Java Province. Meanwhile, in the achievement of MSS DM, as many as 7 out of 38 districts/cities in East Java Province still have not reached the total percentage of achievement of the MSS DM target.